Sicherheit als Standortfaktor: Wirtschaftsbezogene Kriminalität im Ruhrgebiet - Hombach, Bodo; Richter, Frank (Tectum Verlag, 2026)
The Ruhr region is not only one of Germany’s most populous regions, but also a major economic hub home to internationally active DAX-listed corporations and innovative small and mediumsized enterprises. This economic strength makes the region a soughtafter location, but it also presents opportunities for criminal organisations. This volume examines, from the perspectives of the police, academia, business and politics, how security influences the competitiveness and attractiveness of the Ruhr region and what challenges companies in the region face. With contributions from Klaus-Stephan Becker | Ulrich Brettermann | Britta Brisch | Frank Dudda | Bodo Hombach | Guido Kerkhoff | Christoph Kleinschnitz | Christian Kullmann | Thomas Kufen | Sören Link | Herbert Reul | Frank Richter | Frank Schneider | Arndt Sinn | Rolf Wagener